Hemispheric asymmetries in word recognition as revealed by the orthographic uniqueness point effect - Izura, Cristina; Wright, Victoria; Fouquet, Natalie (Frontiers in Psychology, 2014)
The orthographic uniqueness point (OUP) refers to the first letter of a word that, reading from left to right, makes the word unique. It has recently been proposed that OUPs might be relevant in word recognition and their influence could inform the long-lasting debate of whether – and to what extent - printed words are recognised serially or in parallel. The present study represents the first investigation of the neural and behavioural effects of OUP on visual word recognition. Behaviourally, late OUP words were identified faster and more accurately in a lexical decision task. Analysis of ERPs demonstrated a hemispheric asymmetry on the N170 component, with the left hemisphere appearing to be more sensitive to the position of the OUP within a word than the right hemisphere. These results suggest that processing of centrally-presented words is likely to occur in a partially parallel manner, as an ends-in scanning process.